Integrated analysis of competitive endogenous ribose nucleic acids (ceRNAs)-related regulatory networks in invasive and non-invasive non-functioning pituitary adenomas (NFPAs) - Liu, Jiangtao; Wang, Kaixuan; Ji, Hongming; Zhang, Gangli; Chen, Shengli; Zhang, Shiyuan; Lu, Fake; Hu, Changchen (Frontiers in Surgery, 2022)
Background: The aim of this study was to identify the differential noncoding RNA (ncRNA) and mRNA expression profiles and competitive endogenous RNA (ceRNA)-related regulatory networks in invasive and non-invasive nonfunctional pituitary adenomas (NFPAs). Material/Methods: We carried out full-transcriptome sequencing of invasive and non-invasive NFPAs to evaluate their circular RNA (circRNA), long noncoding RNA (lncRNA), micro RNA (miRNA), and mRNA expression profiles. Results: According to the screening criteria, 118 differentially expressed (DE)circRNAs (88 up-regulated and 30 down-regulated), 105 DElncRNAs (68 up-regulated and 37 down-regulated), 43 DEmiRNAs (22 up-regulated and 21 down-regulated), and 268 DEmRNAs (194 up-regulated and 74 down-regulated) were obtained. On this basis, we constructed a ceRNA regulatory network related to invasive NFPA. Gene Ontology and Kyoto Encylopedia of Genes and Genomes analyses showed that circRNAs and lncRNAs in the network were related to chromatin remodeling and participated in the Janus kinase-signal transducer and activator of transcription and calcium signaling pathways. Hsa-miR-1248 had the highest connectivity in the ceRNA regulatory network, and may thus be closely related to the invasiveness of NFPAs. Conclusions： The results of this study clarify the regulatory mechanism of invasive and non-invasive NFPAs, and provide novel research avenues and therapeutic targets for invasive NFPAs.